The effects of information, interaction and design qualities of travel and tour websites on Malaysian tourists’ usage satisfaction - Abdul Latif, Samshul Amry; Borahan, Nur Saiful Amree (Kulliyyah of Languages and Managements (KLM), 2021)
The purpose of this study is to examine the relationships and effects of information, interaction and design qualities of travel and tour websites on Malaysian tourists’ usage satisfaction. This study adopted a convenience sampling method, employing self‐administered online questionnaire approach targeting Malaysian tourists who have used any travel and tour websites. The 200 samples obtained were analyzed using multiple regression analysis using SPSS version 26. Information and interaction qualities of travel and tour websites were found to be significant factors to tourists’ usage satisfaction. Future studies could investigate the rural population in Malaysia as access and coverage to technology may be limited.